2023
DOI: 10.3390/toxins15030232
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Alleviates Aflatoxin B1-Induced Oxidative Stress and Apoptosis in IPEC-J2 Cells via the Nrf2 Signaling Pathway

Abstract: Aflatoxin B1 (AFB1), a typical fungal toxin found in feed, is highly carcinogenic. Oxidative stress is one of the main ways it exerts its toxicity; therefore, finding a suitable antioxidant is the key to reducing its toxicity. Astaxanthin (AST) is a carotenoid with strong antioxidant properties. The aim of the present research was to determine whether AST eases the AFB1-induced impairment in IPEC-J2 cells, and its specific mechanism of action. AFB1 and AST were applied to IPEC-J2 cells in different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Many researchers have used polyphenols to detoxify mycotoxins. Studies have shown that astaxanthin can decrease the impact of aflatoxin B1 on oxidative stress and apoptosis in IPEC-J2 cells [ 33 ]. Similarly, RES protects IPEC-J2 cells from DON-induced injury through the Nrf2 signaling pathway [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have used polyphenols to detoxify mycotoxins. Studies have shown that astaxanthin can decrease the impact of aflatoxin B1 on oxidative stress and apoptosis in IPEC-J2 cells [ 33 ]. Similarly, RES protects IPEC-J2 cells from DON-induced injury through the Nrf2 signaling pathway [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with Kochi et al who previously showed an increased expression of Gpx1 in mouse colonic mucosa [ 57 ]. Similarly, Tian et al reported AST’s ability to decrease aflatoxin B1-induced oxidative stress, increasing NQO1 expression in IPEC-J2 cells [ 31 ]. The results are also consistent with Davinelli et al, who demonstrated AST’s ability to regulate, in humans, the redox-sensitive transcription factor, nuclear factor erythroid 2-related factor 2 (Nrf2), which coordinates the expression of a battery of defensive genes encoding antioxidant proteins and detoxifying enzymes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Szczepanik et al recently demonstrated that AST addition is able to reduce free radicals and protect porcine cells from oxidative damage [ 30 ]. The molecular mechanisms involved in these beneficial effects are under elucidation and, for this purpose, commercially available human (Caco-2 and HT-29) as well as pig (IPEC-J2) cell lines have been used to develop in vitro models [ 31 , 32 , 33 , 34 , 35 , 36 ]. In addition, all these studies have been performed using in vitro 2D culture systems that only partially reflect the complexity of the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commercially valuable carotenoids is astaxanthin, which can be obtained from marine microorganisms and is used as an additive to animal feed, and as a food supplement for humans, and some that produce microorganisms are Agrobacterium aurantiacum and Altererythrobacter ishigakiens [42]. Studies on the possible uses of astaxanthin are diverse, but the most notorious are those found in the medical field since there is talk of its potential as an antioxidant and its anti-inflammatory activity, because it exerts protective effects on liver cells after the induction of inflammation [43], and protects neuronal cells from oxidative stress through the activation of specific pathways [44]. Recent studies have demonstrated the beneficial effects of carotenoids for the treatment of neurodegenerative diseases, while several epidemiological studies have linked the consumption of a diet rich in carotenoids with a reduced risk of neurodegenerative diseases in humans [45].…”
Section: Pigmentsmentioning
confidence: 99%